Anthropology and beauty
1 online resource (xv, 516 pages)
Keywords: "Organised around the theme of beauty, this innovative collection offers insight into the development of anthropological thinking on art, aesthetics and creativity in recent years. The volume incorporates current work on perception and generative processes, and seeks to move beyond a purely aesthetic and relativist stance. The essays invite readers to consider how people sense and seek out beauty, whether through acts of human creativity and production; through sensory experience of sound, light, touch, or experiencing architecture; visiting heritage sites or ancient buildings; experiencing the environment through 'places of outstanding natural beauty'; or through cooperative action, machine-engineering or designing for the future."--Provided by publisher.